2017
DOI: 10.1016/j.molcel.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of mRNA Turnover Revealed by Single-Molecule Imaging in Single Cells

Abstract: RNA degradation plays a fundamental role in regulating gene expression. In order to characterize the spatiotemporal dynamics of RNA turnover in single cells, we developed a fluorescent biosensor based on dual-color, single-molecule RNA imaging that allows intact transcripts to be distinguished from stabilized degradation intermediates. Using this method, we measured mRNA decay in single cells and found that individual degradation events occur independently within the cytosol and are not enriched within process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
157
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 68 publications
(67 reference statements)
8
157
1
1
Order By: Relevance
“…We recently identified the transcriptome and proteome of PBs purified from human cells. Their analysis showed that human PBs are broadly involved in mRNA storage rather than decay [2,3], as also observed using fluorescent decay reporters [4]. However, the mechanism underlying the large but specific targeting of mRNAs to PBs is still unknown, though it clearly results in the co-recruitment of particular RBPs [2].…”
Section: Introductionmentioning
confidence: 79%
“…We recently identified the transcriptome and proteome of PBs purified from human cells. Their analysis showed that human PBs are broadly involved in mRNA storage rather than decay [2,3], as also observed using fluorescent decay reporters [4]. However, the mechanism underlying the large but specific targeting of mRNAs to PBs is still unknown, though it clearly results in the co-recruitment of particular RBPs [2].…”
Section: Introductionmentioning
confidence: 79%
“…The MS2-MCP system has been used in conjunction with other binary systems like the ones provided by PP7 stem-loops and PP7 protein to visualize transcripts undergoing pioneering round of translation (Halstead et al, 2015) or to study the dynamics of mRNA turnover (Horvathova et al, 2017). These methods however do not allow high temporal resolution of mRNA translation due to the time needed for the synthesis of the fluorescent protein.…”
Section: New Technologies To Study Mrna Expression In Neuronsmentioning
confidence: 99%
“…Therefore, actively-translating mRNAs generate two fluorescence signals, whereas untranslated mRNAs only generate an RFP signal. In addition to reporters of translation, a biosensor called TREAT (3’-RNA end accumulation during turnover) has been developed to track mRNA turnover in eukaryotes ((126, 141)). In this approach, the 3’UTR is engineered to include two viral pseudoknots (PKs) flanked by PP7 and MS2 binding sites (Figure 3E).…”
Section: Emerging Strategies and Approachesmentioning
confidence: 99%
“…Such physical magnification leads to an enhanced effective spatial resolution (126, 141). Recently, expansion microscopy has been combined with FISH imaging of RNA (144) in addition to immunofluorescence, and iterative expansion microscopy further enhances resolution from ~70 nm to ~25 nm (145).…”
Section: Emerging Strategies and Approachesmentioning
confidence: 99%